2019
DOI: 10.1002/jum.15210
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Vascular Compromise Using Ultrasound After Free Tissue Transfer

Abstract: Objectives-To report the clinical utility of high-resolution ultrasound (US) for monitoring vascular compromise after free tissue transfer.Methods-Fifty-two tissue transfers in the extremities were included in this study. Blood flow around the anastomotic pedicle and subcutaneous tissue of the grafted flap was monitored with pulsed color and power Doppler US whenever the conventional monitoring method, comprising the bedside assessment of the temperature, capillary refill, and flap color, showed abnormalities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…1–4 There are many conventional modalities used to monitor blood circulation of a flap, including but not limited to handheld Doppler ultrasonography, flap skin temperature measurement, flap skin color tone monitoring, capillary refilling test, and pinprick examination. 4–7 Although previous reports have shown that use of these clinical monitoring modalities during the first few postoperative days increases flap salvage rates from 40 to 80 percent, 4–7 they also have many limitations.…”
mentioning
confidence: 99%
“…1–4 There are many conventional modalities used to monitor blood circulation of a flap, including but not limited to handheld Doppler ultrasonography, flap skin temperature measurement, flap skin color tone monitoring, capillary refilling test, and pinprick examination. 4–7 Although previous reports have shown that use of these clinical monitoring modalities during the first few postoperative days increases flap salvage rates from 40 to 80 percent, 4–7 they also have many limitations.…”
mentioning
confidence: 99%
“…Postoperative monitoring of free flaps for potential arterial or venous compromise is a critical component of free tissue transfer procedures. Unless these complications can be successfully salvaged, achieving a high success rate remains challenging [ 34 , 35 ]. A study by Shinomiya et al found that revascularization surgeries performed within 4 h of diagnosing vascular compromise achieve a higher salvage rate compared to those conducted at 9 h, underscoring the importance of early, accurate detection of postoperative flap complications [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These measures, however, are highly subjective and can lead to the misdiagnosis of compromised flaps. 13 14 Newer modalities such as hand-held Doppler and implantable Doppler have been employed in many institutions for routine monitoring. 12 14 Utilizing audible signals to suggest vessel patency, both are practical tools that allow for rapid identification of threatened flaps, but are not without limitations.…”
Section: Free Flap Monitoring and Perfusionmentioning
confidence: 99%
“…13 14 Newer modalities such as hand-held Doppler and implantable Doppler have been employed in many institutions for routine monitoring. 12 14 Utilizing audible signals to suggest vessel patency, both are practical tools that allow for rapid identification of threatened flaps, but are not without limitations. Handheld Doppler, for example, lacks the ability to differentiate between venous and arterial signals originating from a microsurgical anastomosis and those stemming from the surrounding superficial vasculature.…”
Section: Free Flap Monitoring and Perfusionmentioning
confidence: 99%